Pollutant degradation wastewater treatment device - ZHANG XIN (2017)
A pollutant degradation wastewater treatment device comprises a sludge tank and a hydrolysis tank, wherein the upper opening of the sludge tank is lower than the upper opening of the hydrolysis tank, a lifting machine is installed between the sludge tank and the hydrolysis tank and consists of two power wheels, a chain plate type conveying belt and fixing bowls, the power wheels are respectively installed in the sludge tank and the hydrolysis tank, the chain plate type conveying belt is arranged between the power wheels, a plurality of fixing bowls are installed on the surface of the chain plate type conveying belt, the openings of the fixing bowls located at the upper portion of the chain plate type conveying belt are upward, a horizontal first hydraulic cylinder is installed at the upper portion of the sludge tank, a vertical scraping plate is installed at the end of a piston rod of the first hydraulic cylinder, a support is installed at the upper portion of the lifting machine, and a vertical second hydrau